In the solitude of the taxi: Drivers who have fallen victim to ETA terrorism - Madueño Álvarez, Miguel; Re, Matteo (Hispania Nova, 2022)
In the following article, the authors analyse the assassination of taxi drivers by the terrorist group ETA. Based on primary sources, they consider the attacks against these workers as a form of social control through the dissemination of fear to which ETA subjected those members of the public who might have had any contact with the state security forces. Likewise, the constant harassment of the taxi trade was part of a strategy aimed at isolating police officers and the Guardia Civil, creating a vacuum and hostile opposition around them.